In vitro cytotoxicity effects of single and combination Nigella sativa and Zingiber zerumbet extracts on human myeloid leukemia (HL60) cells and its mode of cell death - Norfazlina M.N. & , Farida Zuraina M.Y., Rajab N.F, Mohd Nazip S., Rumiza A.R., Suziana Zaila C.F. & , Lek Mun L., Nurshahirah N. & , Florinsiah L. & (Journal of Applied Pharmaceutical Science, 2014)
Human myeloid leukemia (HL60) cell line is the precursor and the attractive model of human cell for studying molecular event drug evaluation and cell differentiation. This research investigate the interactive effects between Nigella sativa (Ns) and Zingiber zerumbet (Zz) treated on HL60 cell line for 24 hours at non constant ratio of combination doses. To explain cytotoxicity effect of single and combination extracts is using 3-[45-dimethylthizol-2-yl]-25-diphenyltetrazolium bromide (MTT) assay. The combination of Ns and Zz at various combination doses setting showed the antagonism interactive effects. Ns and Zz showed more potent as anti proliferative agent when treated alone as compared to co-administrations of both. As single agent the IC50 of Ns (Petroleum ether extract) is 654.9ug/ml which is less cytotoxic as compared to Zz (Hexane extract) that inhibit 50% of HL60 viable cells at 63.72ug/ml (p
Keywords: Human myeloid leukemia (HL60), Nigella sativa (Ns), Zingiber zerumbet (Zz), 3-[45-dimethylthizol-2-yl]-25-diphenyltetrazolium bromide (MTT), Apoptosis.